2002
DOI: 10.1210/endo.143.2.8639
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Vascular Endothelial Growth Factor by IGF-I in Osteoblast-Like Cells Is Mediated by the PI3K Signaling Pathway through the Hypoxia-Inducible Factor-2α

Abstract: IGF-I is known to stimulate the expression of oxygen- and nutrient-sensitive genes in several cell types. In this study we investigated the signaling pathways and transcriptional mechanisms that mediate IGF-I induction of vascular endothelial growth factor (VEGF) expression in human osteoblast-like cells. IGF-I (50 ng/ml) induced a rapid increase (3-fold) in VEGF mRNA in osteoblasts that was accompanied by an increase in the level of hypoxia-inducible factor-2alpha (HIF-2alpha) protein without changes in HIF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 34 publications
(26 reference statements)
3
57
0
2
Order By: Relevance
“…1D). This finding is consistent with reports that expression of HIF-2α by breast cancer cells was unaffected by PI3K inhibition (21), although in other cell types, HIF-2α was reported to be IGF-inducible (22,23).…”
Section: Igf1r Depletion Inhibits Cc-rcc Cell Survival and Expressionsupporting
confidence: 93%
“…1D). This finding is consistent with reports that expression of HIF-2α by breast cancer cells was unaffected by PI3K inhibition (21), although in other cell types, HIF-2α was reported to be IGF-inducible (22,23).…”
Section: Igf1r Depletion Inhibits Cc-rcc Cell Survival and Expressionsupporting
confidence: 93%
“…Previous studies have shown that insulin-like growth factor activates EPAS1 in osteoblast-like cells (28). Thus, to understand the molecular basis by which EPAS1 promotes adipose differentiation, we next examined the effects of EPAS1-(1-485) on the expression of genes for insulin signaling and glucose transport.…”
Section: The Combination Of the Ppar␥ Activator And A Conventional DImentioning
confidence: 99%
“…In addition to these roles, a contribution of EPAS1 to the regulation of adipogenesis has been suggested for the following reasons. First, several growth factors, including insulin and insulin-like growth factor, induce and activate EPAS1 activity in a phosphatidylinositol 3-kinase-dependent or related manner (28). Also, HIF-1␣, which is closely related to EPAS1, mediates insulin signaling in hepatocytes (29).…”
mentioning
confidence: 99%
“…A number of growth factors (21,22) and paracrine factors (23)(24)(25)(26) activate the Hif-1 pathway in several cell types under normoxia. In osteoblasts, insulin-like growth factor-1 stabilizes Hif␣ via a mechanism that involves PI3-kinase/Akt signaling (27), and the expression of Hif-1␣ is necessary for normal osteoblast proliferation (28). Additionally, mechanical signals prevent the degradation of Hif ␣-subunits in both skeletal and cardiac muscle (29,30).…”
mentioning
confidence: 99%